PENGEMBANGAN POTENSI DIRI MELALUI METODE DZIKIR DAN OLAH NAPAS (PENELITIAN PADEPOKAN PERISAI BATHIN DAN SILAT LADUNI DI KAB. BANDUNG BARAT) - Anwar Supenawinata (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2014)
Every human being has potencies that needs to be empowered, which is the element of earth, fire, water, and air. Basically these elements consist of two aspects, namely, inner aspects what we called the soul and outer aspects that is the body. Elements of the inner aspects which are water, fire and air, while an element of the outer aspect is land. To process the four elements, it’s required struggle and continuous training so that it could benefit themselves, especially in the implementation of worship, as well as beneficial to others.